Pengaruh Body Image terhadap Psychological Well- Being pada Penggemar K-Pop Generasi Z di Kota Karawang - Rafidatul Fitria Nurohmah; Wina Lova Riza; Ananda Saadatul Maulidia (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine the influence of body image on psychological well-being among Generation Z K-pop fans in Karawang. Using a quantitative approach and a causal associative research design, the study involved 351 respondents who are K-pop fans residing in Karawang. The sampling technique employed was convenience sampling, which allows for the selection of respondents based on accessibility. The measurement tool used for assessing psychological well-being is a scale based on the dimensions proposed by Ryff, which includes self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth. This scale is designed to assess an individual’s psychological well-being comprehensively. Meanwhile, body image was measured using the Multidimensional Body Self-Relation Questionnaire-Appearance Scale (MBSRQ-AS) developed by Cash and Pruzinsky. This scale evaluates how individuals perceive their bodies, including aspects of body satisfaction and physical appearance. The data were analyzed using normality tests, linearity tests, and simple linear regression tests to examine the relationship between body image and psychological well-being. The results showed a significance value of 0.000, which is smaller than 0.05. This indicates that the alternative hypothesis (Ha) is accepted, and the null hypothesis (H0) is rejected, meaning there is a significant effect of body image on psychological well-being among Generation Z K-pop fans in Karawang. Additionally, the coefficient of determination test revealed that body image contributes 40.8% to psychological well-being among K-pop fans. This finding suggests that a positive body image can improve psychological well-being, highlighting the importance of maintaining a healthy body image for supporting mental health among Generation Z. The findings offer valuable insights into the relationship between body image and mental health among K-pop fans in Karawang.